The ethanol extract of Sargassum duplicatum as an ovicidal agent against Aedes aegypti - Giyantolin, Giyantolin; Subiakto, Yuli; Poerwanto, Soenarwan H. (Narra J, 2024)
Dengue hemorrhagic fever (DHF) is a major health concern in tropical and subtropical countries. Indonesia has DHF cases perennially every year. On the other hand, Indonesia is abundant with seaweed (Sargassum duplicatum), which can be found across its seashore. The macroalgae contains secondary metabolites with ovicidal activity; hence, it has the potential to be utilized in suppressing the Aedes aegypti. The aim of this study was to determine the ovicidal activity of S. duplicatum against the Ae. aegypti eggs. The algae were macerated with ethanol 70% before being subjected to qualitative phytochemical screenings. The ovicidal tests were conducted with an extract concentration of 50 ppm, 100 ppm, 500 ppm, 1000 ppm, and 1500 ppm, while distilled water was used as the control. The hatchability of Ae. aegypti was observed 24 hours a day for 4 days and the larval development was investigated under a microscope. Phytochemical screenings revealed that the extract was positive containing alkaloids, flavonoids, steroids, saponins, and phenols. The hatchability of Ae. aegypti eggs were significantly reduced following the S. duplicatum extract exposure for four days (p=0.000). The extract had LC50 of 828.653 ppm and LC50 of 1786.09 ppm for the ovicidal activity against Ae. aegypti eggs. The concentration of ethanol extract of S. duplicatum did not affect the mosquito development from larvae to adult stage (p=0.263). Further research is needed to explore the effect of specific compounds contained in the S. duplicatum and investigate their ovicidal potential.